2007
DOI: 10.1007/s00264-006-0312-7
|View full text |Cite
|
Sign up to set email alerts
|

Handgun injuries with metacarpal and proximal phalangeal fractures: early definitive treatment

Abstract: Most gunshot injuries to the hand involve a combination of tissue types. The goal of this study is to report the results of early definitive treatment in extra-articular metacarpal and proximal phalangeal fractures due to low velocity gunshot wounds and to analyse their outcomes. A retrospective analysis of 51 metacarpal and 41 proximal phalangeal fractures of 76 patients due to low velocity gunshot wounds treated between January 2001 and December 2004 was carried out. We applied acute fixation in the first 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…In addition to a long hospital stay, there are some restrictive conditions, such as the need for high-level surgical skills with a well-organized patient care team. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a long hospital stay, there are some restrictive conditions, such as the need for high-level surgical skills with a well-organized patient care team. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…In addition to a long hospital stay, there are some restrictive conditions, such as the need for high-level surgical skills with a well-organized patient care team. [19] Distal-based fasciocutaneous flaps on the forearm have proven to be simple use, versatile and reliable flaps; they can be used to reconstruct a wide variety of soft tissue defects of the hand. [20] In this sense, PIF has aroused increasing interest in plastic hand surgeons and is one of the most frequently used skin flaps in reconstructive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…This problem has by no means been solved. Kömü rcü et al found good results with both plating and external fixation in both phalanges and metacarpals injured with low-velocity gunshots (Level IV Evidence), 16 while Bach et al demonstrated acceptable results using a locked intramedullary nail in the metacarpal with missing bone (Level V Evidence). 17 In terms of other methods of metacarpal fixation, acceptable results have been demonstrated with a variety of other techniques.…”
Section: Nonthumb Metacarpalsmentioning
confidence: 97%
“…Kiehn [19], in a restrospective descriptive study, pointed immediate definitive fixation methods and the best choice for definitive fixation in hand fractures by low energy firearms. Komurcu [20] compared osteosynthesis with plate and fixation with kirschner wires in hand fractures by low velocity firearms, in a total of 76 patients, 51 metacarpal fractures and 41 proximal phalangeal fractures. There were no significant differences between the methods used.…”
Section: Gustillo III Gunshot Fracturesmentioning
confidence: 99%